When do Interlocks Matter? Institutional Logics and the Diffusion of Multiple Corporate Governance Practices - Shipilov, Andrew V.; Greve, Henrich R.; Rowley, Timothy J. (Academy of Management Journal, 2010)
Despite the wealth of research on the origins of institutions, little is known about how institutions and their underlying logics are extended following initial diffusion. We argue that institutional extension happens through multiwave diffusion of related practices that is such that an organization's adoption of practices from an institutional logic implies its acceptance of the logic. This makes organizational adoption of subsequent practices sharing the same logic more likely, irrespective of these practices' adoptions by the organization's network contacts. We show evidence of such effects though analyzing the diffusion of governance practices related to the logic of board reform in Canada.